Interpretation at the Tokyo War Crimes Tribunal: An Overview and Tojo’s Cross-Examination - Watanabe, Tomie (TTR)

(untitled) (Association canadienne de traductologie, 2009)
The Tokyo and the Nuremberg War Crimes Tribunals were two major international military tribunals organized immediately after World War II. Interpretation at the Nuremberg Trial has been described in a number of papers and books and is considered the origin of simultaneous interpretation. However, with regards to the Tokyo Trial, only the inadequate quality of interpretation has been mentioned in history books and political science publications, and this on very few occasions. This paper begins by offering an overview of the interpretation at the Tokyo Trial through interviews and the records of the proceedings and then analyzes a particular instance of interpretation, namely the cross-examination of Hideki Tojo, who was tried for his significant role in WWII as Minister of War and Prime Minister, and who was finally sentenced to death by the court.The Tokyo Trial was the first instance of an IBM Public Address System (simultaneous interpreting equipment) being installed with an interpreter’s booth in Japan. However, we must recall that it was actually consecutive interpretation that was provided through the use of the IBM system and the booth. Therefore the Tokyo Trial is the origin of the use of simultaneous interpretation equipment, but not the origin of simultaneous interpretation skills in Japan.The records of the proceedings show that twenty-seven Japanese served as interpreters. They were selected on the basis of their good command of English but were definitely laymen in terms of interpretational skills. In order to supervise the Japanese interpreters, four monitors were appointed by the Allied Powers. The monitors, who were second generation Japanese residents in the US, worked for ATIS (Allied Power’s Translation and Interpretation Section) during WWII and were then considered to have a good knowledge of the Japanese language, culture and history. Furthermore, the Language Arbitration System was established to address intractable translation issues related to Japanese culture and pre-war systems. The quality of the interpretation, as far as Tojo’s cross-examination is concerned, can be considered fairly good, if we consider that interpreters and monitors worked together as one unit in the interpretation service. The analysis of the interpretation based on the monitors’ interventions in Tojo’s cross-examination indicates that the monitors were concerned with the accuracy of the English interpretation in court and with the understandability of the Japanese interpretation for the accused and worked to ensure a fair trial.